2020
DOI: 10.1021/acsaelm.0c00449
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Highly Efficient Electron Emission from a Graphene/Oxide/Semiconductor Structure

Abstract: Highly efficient electron emission of 48.5% was demonstrated by a graphene/oxide/semiconductor (GOS) structure. The main factors contributing to this performance were investigated by analyzing the energy distributions of the emitted electrons and the current conduction mechanism through the oxide layer. The energy level of the lower tail of the electron energy distribution was 2.4−2.6 eV above the work function of the graphene electrode, indicating that the work function of the gate electrode does not affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 60 publications
(110 reference statements)
1
17
0
Order By: Relevance
“…Cold electron sources that can be microfabricated on chips have been another pursuit for more than 50 years, as they can work at room temperature and facilitate scaling down and integration of EB-based devices and instruments. Field emission sources have been intensively studied for this purpose and exhibit several advantages, including efficient and dense electron emission. , In addition to field emission sources, tunneling electron sources (TESs) based on the emission of hot electrons generated in tunneling junctions are another long-term-studied and promising candidate for such cold electron sources. In contrast to the prerequisite for UHV for field emission sources, tunneling emission has been demonstrated to be independent of pressure from 10 –6 to 1 Pa, as it is governed by the electric field inside the insulator and planar electron-emitting surfaces with low air reactivity are employed. However, TESs have in common the requirement of a diode-type structure to apply a voltage to the tunneling junction for hot electron generation and the issue that hot electrons are mostly thermalized before emission due to unavoidable inelastic scattering .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cold electron sources that can be microfabricated on chips have been another pursuit for more than 50 years, as they can work at room temperature and facilitate scaling down and integration of EB-based devices and instruments. Field emission sources have been intensively studied for this purpose and exhibit several advantages, including efficient and dense electron emission. , In addition to field emission sources, tunneling electron sources (TESs) based on the emission of hot electrons generated in tunneling junctions are another long-term-studied and promising candidate for such cold electron sources. In contrast to the prerequisite for UHV for field emission sources, tunneling emission has been demonstrated to be independent of pressure from 10 –6 to 1 Pa, as it is governed by the electric field inside the insulator and planar electron-emitting surfaces with low air reactivity are employed. However, TESs have in common the requirement of a diode-type structure to apply a voltage to the tunneling junction for hot electron generation and the issue that hot electrons are mostly thermalized before emission due to unavoidable inelastic scattering .…”
mentioning
confidence: 99%
“…First, hot electrons in our device encounter less restriction in space than those in a conventional TES. A conventional TES generally employs vertically stacked metal (or semiconductor)–insulator–metal (or semiconductor) tunneling junctions, where hot electrons are generated in the buried insulator layer and have to be transported across the above metal (or semiconductor) layer before emission (Figure S1). Hot electrons with sufficient energy for emission in the insulator mostly cannot be finally emitted into vacuum, as they are thermalized due to inelastic scattering during their transport across the above metal (or semiconductor) layer, which works as a blocking layer, giving strong spatial restriction on electron emission.…”
mentioning
confidence: 99%
“…However, LMF emissivity of nanogranular metal thin films manifested without any additional energizing had been previously reported, e.g., by Purohit et al [86,87]. Moreover, several of the early experiments with MOS sandwich films discussed above employed relatively high magnitudes of extracting electric field applied to emitting structure surface: 5 kV/10 mm in [41], 1000 V/5 mm in [26], etc. This is comparable with threshold field values for the best samples tested in the present work, and the emission, observed in those experiments, could have been caused, at least partially, by the direct action of the applied field, not by the feeding current.…”
Section: Comparison With Literature Datamentioning
confidence: 87%
“…Later, with refined technologies, the properties of MIM/MOS cathodes were significantly improved [22,23], while the emission mechanism apparently came into agreement with the original concept [15]. The most recent progress was related to the idea of using graphene (G) films as top electrodes [24][25][26]; Murakami et al reported on the achievement of emission efficiency up to ~50% and current densities >100 mA/cm 2 with the GOS structures [26].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation